Analysis of G+30 Building Structure Using Etabs in Zone IV and Zone V (International Journal of Food and Nutritional Sciences, 2022)
Since the beginning of time, we have known that earthquakes can result in disasters. Buildings of today are becoming ever more slender and prone to sway, making them more dangerous during an earthquake. In the past, engineers and scientists came up with ways to make buildings more resistant to earthquakes. The ETABS software package's use of lateral load resisting techniques in the building configuration has significantly improved the structure's earthquake resistance, according to a number of practical studies. Shear walls and bracings were used in various situations for the work, and the highest level taken into consideration for the purpose of the study is 93.5 meters.The modeling is finished with an eye toward how certain conditions and specific heights will be affected by seismic factors like story drift, shear force, building torsion, bending moment, and time. The acquired knowledge has been implemented for Zone IV in Soil Type II (medium soils) in accordance with IS 1893-2002.